Improving Image Quality in Hero Photos Using Grayscale Images Using the Histogram Equalization Method - Rina Afriani Sitorus; Yunda Aidilia; Yustria Handika Siregar (Bigint Computing Journal, 2023)
Photos of heroes are one of the important images in history. Today's hero photos have poor image quality because the camera technology that existed in the past was still simple. Due to technological limitations at that time, the current hero photos are still of low quality with the dominant color being gray. This condition results in the information contained sometimes not being received properly. To overcome this problem, it is necessary to improve the image quality of hero photos which are still of low quality. Image quality improvement is one of the image processing operations which aims to perfect the image by manipulating image parameters. This operation is often applied to images that have poor quality so that the quality can be improved. In this research, we will apply image enhancement operations or improve the image quality of hero photos so that the quality can increase. There are many methods that can be used to enhance images, one of which is histogram equalization which has been widely used to enhance images, especially greyscale images. This method is usually done on images using the Matlab application because of its simple use. This research produces new images with better quality than previous images